2021
DOI: 10.1093/tropej/fmab053
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Effects and Predictive Factors Affecting the Clinical Severity of Scorpion Envenomations in Western Turkey

Abstract: Background Scorpion envenomation is a common medical emergency in many countries, including Turkey. Severe systemic symptoms occur more easily in children and mortality rates are higher. The aim of this study is to describe the clinical effects and predictive factors affecting the clinical severity of scorpion envenomations in Western Turkey. Methods Two hundred one children (138 mild cases, 34 moderate, and 29 severe) with s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 36 publications
1
12
0
1
Order By: Relevance
“…Among these, respiratory distress [ 26 , 28 , 34 , 36 38 , 40 , 43 48 , 51 , 59 , 63 71 , 73 92 ] and increased heart rate (tachycardia) [ 13 , 27 , 34 , 36 39 , 43 , 44 , 47 , 53 , 56 , 58 , 59 , 61 , 64 66 , 68 , 69 , 74 , 75 , 77 – 89 ] were the most common manifestations affecting 94.8% (145 from 153) and 82% (137 from 167) of the patients, respectively. In studies where the prevalence of pulmonary edema could be determined unequivocally, it was observed in 60.7% (246 from 405) of patients [ 13 , 27 , 34 , 36 39 , 42 44 , 47 , 48 , 51 , 56 , 58 , 59 , 64 66 , 69 , 75 ,…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among these, respiratory distress [ 26 , 28 , 34 , 36 38 , 40 , 43 48 , 51 , 59 , 63 71 , 73 92 ] and increased heart rate (tachycardia) [ 13 , 27 , 34 , 36 39 , 43 , 44 , 47 , 53 , 56 , 58 , 59 , 61 , 64 66 , 68 , 69 , 74 , 75 , 77 – 89 ] were the most common manifestations affecting 94.8% (145 from 153) and 82% (137 from 167) of the patients, respectively. In studies where the prevalence of pulmonary edema could be determined unequivocally, it was observed in 60.7% (246 from 405) of patients [ 13 , 27 , 34 , 36 39 , 42 44 , 47 , 48 , 51 , 56 , 58 , 59 , 64 66 , 69 , 75 ,…”
Section: Resultsmentioning
confidence: 99%
“…Ventricular tachycardia was another important finding [ 71 , 75 , 76 , 84 ]. Laboratory findings associated with myocarditis were raised levels of cardiac troponin T [ 49 , 57 , 61 , 64 , 70 , 72 , 75 , 87 ], troponin I [ 34 , 41 , 42 , 45 , 46 , 49 , 58 , 60 , 65 , 66 , 74 , 76 , 78 , 79 , 81 , 82 , 84 86 , 88 , 91 , 92 ], unspecified-type troponin [ 63 , 67 , 80 , 82 ], CK-MB [ 14 , 18 , 34 , 37 , 40 , 45 , 46 , 49 , 52 , 57 , 59 , 62 , 66 , 68 , 70 , 74 76 , <...…”
Section: Resultsmentioning
confidence: 99%
“…Celik et al, in a study conducted in pediatric patients, have shown that the increase in the leukocyte, neutrophil, PLT and glucose levels of the patients was associated with the severity of the disease 12 . In this study, we observed that WBC, neutrophil, leukocyte and K elevations were associated with the development of serious disease.…”
Section: Discussionmentioning
confidence: 98%
“…PCT and PDW are associated with inflammation [25]. Çelik et al examined scorpion stings in children and showed that increased platelet and PCT values were predictive of serious clinical conditions [26]. In another study, an increased PDW and PDW to lymphocyte ratio showed a poor prognosis in snakebites [19].…”
Section: Discussionmentioning
confidence: 99%